ВПЛИВ ДОБАВКИ VC-Al НА СТРУКТУРУ ТА ФАЗОВИЙ СКЛАД НАДТВЕРДИХ МАТЕРІАЛІВ НА ОСНОВІ cBN - Сліпченко, К. В.; Петруша, І. А.; Туркевич, В. З.; Бушля, В. М.; Штоль, Я.-Е. (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2018)
Ceramic matrix materials based on cubic boron nitride with additives of vanadium carbide and aluminum were obtained by high pressure high temperature sintering. Sintering was carried out under pressure 7.7 GPa, in the wide temperature range of 1450 - 2450 °C. Three compositions containing 50, 60 and 65 vol.% of cBN were selected for investigation, 5% by volume of aluminum introduced into the mixture as oxygen geter. This paper presents the results of the study of the phase composition, microstructures and mechanical properties. It was found that the variation of the additive content has no effect on the shear modulus of composites, the highest values of microhardness were obtained in composites sintered in the temperature range of 1850 - 2150 °C. Formation of aluminum oxide were detected in all studied systems when sinterinf temperature was higher than 2000 °C. Mechanical properties of developed materialsclose to commercial analogues of BL group materials. Cutting tool materials in system cBN-VC-Al can be used at high-speed processing of alloys on the basis of iron